2004
DOI: 10.1074/jbc.m313891200
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Cross-talk between Rac and Cdc42 GTPases Regulates Generation of Reactive Oxygen Species

Abstract: Cross-talk between Rho GTPase family members (Rho, Rac, and Cdc42) plays important roles in modulating and coordinating downstream cellular responses resulting from Rho GTPase signaling. The NADPH oxidase of phagocytes and nonphagocytic cells is a Rac GTPaseregulated system that generates reactive oxygen species (ROS) for the purposes of innate immunity and intracellular signaling. We recently demonstrated that NADPH oxidase activation involves sequential interactions between Rac and the flavocytochrome b 558 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 56 publications
4
82
0
2
Order By: Relevance
“…Members of the Rho family have been recognized as key regulators of signal transduction pathways that mediate changes in the actin cytoskeleton required for transformation (Huang et al, 2004). However, the balance among RhoA, Rac and Cdc42 activities determines whether a given cell remains stationary or becomes migratory (Diebold et al, 2004;Wojciak-Stothard et al, 2005). We found that the decreased UCH-L1 expression caused by RNAi results in disruption of focal adhesion.…”
Section: Discussionmentioning
confidence: 61%
“…Members of the Rho family have been recognized as key regulators of signal transduction pathways that mediate changes in the actin cytoskeleton required for transformation (Huang et al, 2004). However, the balance among RhoA, Rac and Cdc42 activities determines whether a given cell remains stationary or becomes migratory (Diebold et al, 2004;Wojciak-Stothard et al, 2005). We found that the decreased UCH-L1 expression caused by RNAi results in disruption of focal adhesion.…”
Section: Discussionmentioning
confidence: 61%
“…21 Our in situ GST pull-down analysis 15 showed that the activity of RhoA and Rac1/Cdc42 at different indicated time points did not differ from that of control with treatment of either H 2 O 2 or TAT-AM (Figure 4e). Taken together, these data implicate that Nogo-66-NgR/LINGO-1 and RhoA-ROCK signaling pathway do not link to aminoNogo-A-mediated pro-survival role.…”
Section: Resultsmentioning
confidence: 99%
“…28 Paclitaxel-induced microtubule stabilization could activate Nox by a Rac-dependent pathway, since Nox is regulated by the activation of Rac GTPase, a member of Rho GTPase family closely interacting with microtubule. 29,30 However, because DPI inhibits paclitaxel-induced O 2°2 production only partially, Nox is probably not the only source of paclitaxel-induced O 2°2 production. Early mitochondrial O 2°2 production induced by paclitaxel has also been reported both in cell-free system and intact cells, and appears to occur upstream of caspase activation.…”
Section: Discussionmentioning
confidence: 99%